Glioblastoma‐activated pericytes support tumor growth via immunosuppression. (25th February 2018) - Sena, Isadora F. G.; Paiva, Ana E.; Prazeres, Pedro H. D. M.; Azevedo, Patrick O.; Lousado, Luiza; Bhutia, Sujit K.; Salmina, Alla B.; Mintz, Akiva; Birbrair, Alexander
Abstract: Glioblastoma multiforme is the most common and aggressive primary brain tumor, with an extremely poor prognosis. The lack of detailed knowledge about the cellular and molecular mechanisms involved in glioblastoma development restricts the design of efficient therapies. A recent study using state‐of‐art technologies explores the role of pericytes in the glioblastoma microenvironment. Glioblastoma‐activated pericytes develop an immunosuppressive phenotype, reducing T‐cell activation through the induction of an anti‐inflammatory response. Strikingly, pericytes support glioblastoma growth in vitro and in vivo. Here, we describe succinctly the results and implications of the findings reported in pericytes' and glioblastomas' biology. The emerging knowledge from this study will be essential for the treatment of brain tumors. Abstract : Glioblastoma‐activated pericytes develop an immunosuppressive phenotype, reducing T‐cell activation through the induction of an anti‐inflammatory response. Pericytes support glioblastoma growth in vitro and in vivo.